Silencing, invisibilities and gender subversions in A vida invisível de Eurídice Gusmão, by Martha Batalha (Revista Crioula, 2022)
This work analyzes different gender experiences in the book A vida invisível de Eurídice Gusmão, by Martha Batalha. In this essay, we showed that the reality experienced by the protagonist is not the same as the characters who occupy antagonistic or secondary roles, with several levels of gender invisibility. In this sense, what can be considered a form of subversion for Eurídice Gusmão is a daily action of other women in the narrative, who suffer other types of silencing, requiring new forms of resistance.